Recommendations from a thesis: the Cinderella of the final report? - Luis Alberto Corona Martínez; Mercedes Fonseca Fernández (Medisur)
Frequently, insufficient depth is observed in the research recommendations’ preparation. This article addresses two deficiencies in this section of the final report: the omission of recommendations when their existence is evident, and the erroneous or forced declaration of suggestions, not based on the results or conclusions of the study. It is highlighted that, despite the convenience of stating recommendations, the researcher must be very careful in preparing his suggestions.